2017
DOI: 10.1097/mol.0000000000000444
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol reduction and macrophage function: role of paraoxonases

Abstract: Purpose of review Unregulated uptake of oxidized LDL by macrophages to form foam cells is the hallmark for atherosclerosis. The paraoxonase (PON) family of enzymes play a critical role in attenuating atherosclerotic lesion formation by hydrolyzing lipid peroxides (LOOHs) and preventing the oxidation of LDL particles and by enhancing HDL-mediated cholesterol efflux. Findings in recent years suggest novel mechanisms by which PON isoforms interact with macrophages to regulate cholesterol metabolism and cellular f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 46 publications
0
9
0
1
Order By: Relevance
“…HDL particles carry important enzymes, such as paraoxonase, which can exert a protective effect against oxidative damage of circulating lipoproteins and cells [ 43 ]. Among the enzymes of the paraoxonase family, paraoxonase 1 (PON1) and paraoxonase 3 (PON3) are mainly associated with HDL and exhibit paraoxonase, lactonase and esterase activities [ 44 ]. PON1 protects HDL and low-density lipoprotein (LDL) against oxidation, reduces macrophage and aortic oxidative status associated with decreased superoxide anion production, and enhances the reverse cholesterol transport by facilitating the binding of HDL particles to macrophages [ 45 , 46 , 47 , 48 ].…”
Section: Hdl Compositionmentioning
confidence: 99%
See 2 more Smart Citations
“…HDL particles carry important enzymes, such as paraoxonase, which can exert a protective effect against oxidative damage of circulating lipoproteins and cells [ 43 ]. Among the enzymes of the paraoxonase family, paraoxonase 1 (PON1) and paraoxonase 3 (PON3) are mainly associated with HDL and exhibit paraoxonase, lactonase and esterase activities [ 44 ]. PON1 protects HDL and low-density lipoprotein (LDL) against oxidation, reduces macrophage and aortic oxidative status associated with decreased superoxide anion production, and enhances the reverse cholesterol transport by facilitating the binding of HDL particles to macrophages [ 45 , 46 , 47 , 48 ].…”
Section: Hdl Compositionmentioning
confidence: 99%
“…M1 macrophages are regarded as pro-inflammatory and are induced by T helper type 1 (Th1) cytokines, including interferon γ, tumor necrosis factor (TNF) α (TNF-α), IL-2, and LPS. M2 macrophages are implicated in the resolution of inflammation via suppression of cytokine secretion and promotion of wound healing and tissue remodeling [ 44 , 108 ]. Several humoral factors may modify the balance between M1 and M2 phenotypes.…”
Section: Immunomodulatory Functions Of Hdlmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, PON1 inhibits the formation of free radical species in macrophages by preventing the activation of NADPH oxidase and by stabilizing mitochondria. PON1 also promotes the differentiation of macrophages into an anti-inflammatory phenotype [146]. A recent study of note [147] showed that genetically reduced PON1 concentration induces proatherogenic changes in plasma proteomes in humans and mice.…”
Section: Cardiovascular Diseasesmentioning
confidence: 99%
“…As stated before, HDL is described as having the antioxidant ability to prevent or delay the oxidation of LDL due to proteins associated with its surface, such as PON-1, which can prevent the oxidation of HDL, as well as LDL [125][126][127][128][129][130][131][132][133][134][135][136][137]. Again, it is important to note that both PON-1 and PON-3 are components of HDL and that they reduce the atherogenicity of lipoproteins through of hydrolyzing of lipolactones [138,139]. As a result, the uptake of atherogenic lipoproteins by macrophages and the formation of foam cells is reduced [140].…”
Section: Paraoxonase and Cardiovascular Diseasesmentioning
confidence: 99%